Results of a unilateral lip lift for correction of a vertical disproportion in upper lip vascular anomalies - Loghmani Shahriar; Momeni Amir; Eidy Mohammad (Indian Journal of Plastic Surgery, 2009)
Congenital vascular anomalies most notably hemangiomas involving the lips, especially those which fail to regress, pose a difficult problem both for the surgeon and the patient. These lesions not only discolour the skin but may also distort the shape of the lip. When nonsurgical modalities fail to treat these lesions, surgery is chosen as the next viable step. In this article, we propose a well planned sequential surgical procedure for unilateral lesions. This approach in comparison with previously used procedures produces noticeably better results and fewer complications. During a period of 4 years, we treated 21 patients with vascular anomalies using the unilateral upper lip lift procedure to correct the vertical disproportion of commissures. Using this procedure, we managed to restore the normal form and symmetry of the upper lip in a majority of our patients with less obvious scarring and few complications.